What does Twitter say about COVID-19 vaccines? - Snow, Erin; Weir, Natalie; Mueller, Tanja (2023)
Background and objectives: Vaccines to reduce the level of hospitalisations and death from COVID-19 became available in certain countries from December 2020. This study aimed to analyse social media content shared on Twitter regarding COVID-19 vaccines on a random day to obtain insights into publicly expressed opinions on these vaccines. Method: English language tweets, regardless of country of origin, were collected through NCapture from a 24-hour time period between 06/11/2022 and 07/11/2022 using the search term “COVID-19 vaccines”. NVivo aided content analysis was conducted on all obtained tweets; tweets unrelated to the study aim were coded as irrelevant and subsequently excluded from analysis. The study was exploratory in nature, without an underlying hypothesis. Results: Overall, 1284 tweets were captured. A total of 67 different codes were created with 50 of those directly relating to opinions and/or information about COVID-19 vaccines; 41.8% of which were negative and 34.3% positive. Positive tweets related to, e.g., encouraging the public to get the vaccine; reductions in COVID-19 related health burdens; and providing links to scientific studies. In contrast, negative tweets warned of potential dangers associated with vaccines, primarily highlighting side effects; and reiterated prevalent conspiracy theories. Conclusion: Overall, opinions on Twitter regarding COVID-19 vaccines showed considerable variation on the day the tweets were captured. Nevertheless, there was a notable number of tweets providing links to reliable studies on COVID-19 vaccines, indicating that many Twitter users may aim to provide reliable information regarding COVID-19 vaccines.